2020
DOI: 10.1097/tp.0000000000003014
|View full text |Cite
|
Sign up to set email alerts
|

Liver and Kidney Recipient Selection of Hepatitis C Virus Viremic Donors: Meeting Consensus Report From the 2019 Controversies in Transplantation

Abstract: The development of multiple highly effective and safe direct-acting antivirals to treat hepatitis C virus (HCV) has resulted in greater ease and confidence in managing HCV infection in transplant recipients that in turn has impacted the solid organ transplant community as well. In the United States, the opioid epidemic has increased the number of overdose deaths with a concomitant increase in younger HCV viremic donors after brain death being identified. At the same time, a decrease in HCV viremic transplant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…A major breakthrough in the last decade to battle the organ shortage was the practice of transplanting kidneys from HCV-viremic donors into HCV-negative patients (HCV D+/R-) followed by direct-acting antiviral therapy. Early data were promising demonstrating decreased waitlist times and access to younger donors with excellent allograft function [ 65 67 ]. A recent study of the impact of this newly discovered donor pool on racial minorities and women revealed that once again this population continues to be disadvantaged [ 68 ▪ ].…”
Section: Conclusion (Liver)mentioning
confidence: 99%
“…A major breakthrough in the last decade to battle the organ shortage was the practice of transplanting kidneys from HCV-viremic donors into HCV-negative patients (HCV D+/R-) followed by direct-acting antiviral therapy. Early data were promising demonstrating decreased waitlist times and access to younger donors with excellent allograft function [ 65 67 ]. A recent study of the impact of this newly discovered donor pool on racial minorities and women revealed that once again this population continues to be disadvantaged [ 68 ▪ ].…”
Section: Conclusion (Liver)mentioning
confidence: 99%
“…The recent availability of DAAs has led a paradigm shift in the management of posttransplant hepatitis C. DAAs give the opportunity to expand the donor pool for kidney transplant; however, the optimal timing for the initiation of DAA therapy post-kidney transplant is still controversial [50,51]. It is clear that the frequency of AEs is related to various factors including patient selection, among others; nonetheless, it appears from Table 4 that the frequency of AEs is greater when DAAs are not given in the early post-kidney transplant phase.…”
Section: Kidney Transplant From Hcv/nat-positive Donors To Naïve Recipients: Pros and Consmentioning
confidence: 99%
“…BeLIAC consider DAAs as an opportunity to the transplant community to solve the HCV problem in donors but there is ongoing debate of how to make the best use of this landmark medical breakthrough for our patients awaiting a liver transplant (95). Many questions remain to be answered and we clearly need to unit forces to make this new challenge a success story.…”
Section: Definition Of An Hcv+ Donormentioning
confidence: 99%